The transcription factor HMGB2 indirectly regulates APRIL expression and Gd-IgA1 production in patients with IgA nephropathy - Huijuan Tian; Yaling Zhai; Shuaigang Sun; Wenhui Zhang; Zhanzheng Zhao (Renal Failure)
Background IgA nephropathy (IgAN) is the most common primary glomerulonephritis worldwide. Proliferation-inducing ligand (APRIL) was identified as an important cause of glycosylation deficiency of IgA1 (Gd-IgA1), which can ‘trigger’ IgAN. Our previous study indicated that high migration group protein B2 (HMGB2) in peripheral blood mononuclear cells from patients with IgAN was associated with disease severity, but the underlying mechanism remains unclear.Materials and methods The location of HMGB2 was identified by immunofluorescence. qRT-PCR and Western blotting were used to measure HMGB2, HMGA1, and APRIL expression. Gd-IgA1 levels were detected by enzyme-linked immunosorbent assay (ELISA). In addition, we used DNA pull-down, protein profiling, and transcription factor prediction software to identify proteins bound to the promoter region of the APRIL gene. RNA interference and coimmunoprecipitation (Co-IP) were used to verify the relationships among HMGB2, high mobility group AT-hook protein 1 (HMGA1), and APRIL.Results HMGB2 expression was greater in IgAN patients than in HCs and was positively associated with APRIL expression in B cells. DNA pull-down and protein profiling revealed that HMGB2 and HMGA1 bound to the promoter region of the APRIL gene. The expression levels of HMGA1, APRIL, and Gd-IgA1 were downregulated after HMGB2 knockdown. Co-IP indicated that HMGB2 binds to HMGA1. The Gd-IgA1 concentration in the supernatant was reduced after HMGA1 knockdown. HMGA1 binding sites were predicted in the promoter region of the APRIL gene.Conclusion HMGB2 expression is greater in IgAN patients than in healthy controls; it promotes APRIL expression by interacting with HMGA1, thereby inducing Gd-IgA1 overexpression and leading to IgAN.